Science and technology of zirconia - International Conference on the Science and Technology of Zirconia (1st : 1980 : Case Western Reserve University); Heuer, A. H. (Arthur Harold), 1936-; Hobbs, L. W.; Case Institute of Technology. Ceramics Group; American Ceramic Society (Columbus, Ohio : American Ceramic Society)
Includes bibliographical references and indexes.